Method for preparing ferric sodium pyrophosphate material based on regulation and control of valence state of iron source

In the synthesis process of sodium ferric phosphate material, the iron defects and inactive phase m-NFP of the precursor are solved during the charging and discharging process of the material. The problem of high content has achieved the preparation of high-purity NFPP materials and excellent electrochemical properties.

CN119409174AActive Publication Date: 2025-02-11SUZHOU UNIV

Patent Information

Application Number
CN202510020752.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing sodium ferric phosphate pyrophosphate materials have iron defects during charging and discharging, resulting in a decrease in capacity, and the inactive phase m-NFP content generated during synthesis is high, affecting the purity and performance of the material.

Method used

By using 0-valent iron source and +2-valent iron source to regulate the precursor iron source price state, combined with the adjustment of process parameters, we ensure that the iron element valential state in the precursor is +2-valent and +3-valent. During the sintering process, Fe2+ will be first combined with The phosphorus source and sodium source react to produce NFPP. Then Fe3+ is converted to Fe2+ through carbon thermal reduction, and further reacts with the phosphorus source and sodium source to produce high-purity NFPP material.

Benefits of technology

The purity of NFPP pure phase materials is significantly improved, the formation of m-NFP is reduced, the generation of iron defects is avoided, and the high capacity retention rate and excellent electrochemical properties of the material are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409174A_ABST
    Figure CN119409174A_ABST
Patent Text Reader

Abstract

The method comprises the following steps: mixing a zero-valent iron source, a + 2-valent iron source, a carbon source and a solvent, and carrying out a reaction so as to obtain a solution A; adding a sodium source and a phosphorus source into the solution A, and reacting to obtain a solution B; adding a dispersing agent into the solution B, and reacting to obtain a solution C; stirring the solution C to a gel state, and drying to obtain a precursor; and carrying out ball milling treatment on the precursor, pre-sintering at a low temperature under a protective atmosphere, and sintering at a high temperature to obtain the sodium ferric pyrophosphate material. According to the invention, a 0-valent iron source and a + 2-valent iron source are adopted, the valence state of the precursor iron source is regulated and controlled, and the high-purity ferric sodium pyrophosphate positive electrode material is synthesized under a standard stoichiometric ratio, and has a good crystallographic structure and excellent electrochemical performance; meanwhile, the material has the characteristics of low cost, simple preparation and easy large-scale production, and has a relatively good application prospect in the field of electrochemical energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium iron pyrophosphate material preparation, and in particular to a method for preparing the sodium iron pyrophosphate material based on the regulation of the valence state of an iron source. Background Art

[0002] At present, lithium-ion batteries are widely used in the electrochemical energy storage market. However, the high cost of lithium-ion batteries and their poor low-temperature performance restrict their application in large-scale energy storage.

[0003] Compared to lithium, sodium is abundant in the earth's crust, and the physical and chemical properties of sodium and lithium are similar. These properties of sodium make sodium-ion batteries an ideal substitute for lithium-ion batteries. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries, and charge transfer is achieved through the insertion and extraction of sodium ions. Sodium superion conductor (NASICON) structural materials have become a hot topic of research due to their stable three-dimensional main structure, abundant sodium ion insertion interstitial sites and good sodium ion diffusion capacity. Among the many sodium superion conductor structural materials, sodium iron pyrophosphate (Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ))(NFPP) has the characteristics of low cost, long cycle life, green environmental protection, and stable structure. Its theoretical specific capacity can reach 129 mAh / g. It is considered to be one of the most promising polyanion positive electrode materials. Further exploration of its preparation method, material properties, and cost control to reduce costs and increase efficiency will help further promote its commercialization.

[0004] For the synthesis of sodium iron pyrophosphate, under the standard stoichiometric ratio, it is very easy to generate a pyrophosphate-type sodium iron phosphate (m-NFP) hybrid phase. Nanoscale m-NFP is electrochemically active under some conditions, but limited by the synthesis cost, the m-NFP synthesized by most methods is chemically inactive. At present, the mainstream method for synthesizing pure-phase NFPP is iron-deficient treatment, that is, by reducing the iron source content and not synthesizing the material at the standard stoichiometric ratio of the material, in order to reduce the inactive phase (m-NFP) generated by side reactions during the synthesis process. The problem with this method is that the synthesized NFPP pure-phase material has iron defects, which leads to Fe 2+ with Fe 3+ The redox transitions that occur are reduced, which leads to a decrease in capacity. The synthesis of pure phase NFPP materials with standard stoichiometric ratios is expected to further improve the energy density of the materials and promote their industrial development, and its research and development is of great significance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing sodium ferric pyrophosphate material based on the regulation of the valence state of the iron source. The valence state of the precursor iron source is regulated by a 0-valent iron source and a +2-valent iron source in a standard stoichiometric ratio. Combined with the adjustment of process parameters, the valence state composition of the iron source in the precursor is ensured to be most consistent with the synthesis orientation of the NFPP pure phase. The valence state of the iron element in the precursor is +2 and +3. During the sintering process, Fe 2+ First, it reacts with phosphorus and sodium sources. At this time, the synthetic orientation of the material tends to be NFPP rather than m-NFP, and then Fe 3+ The carbothermal reduction reaction converts it into Fe 2+ At this time, it continues to react with the remaining phosphorus source and sodium source to generate NFPP and a small amount of m-NFP, which greatly improves the phase purity of the synthesized NFPP. At the same time, the content of the inactive phase m-NFP in the material is reduced to an extremely small level, and it is ensured that no iron defects are generated. The capacity of the material will not decrease, and a high-purity sodium iron pyrophosphate positive electrode material is synthesized.

[0006] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source, comprising the following steps: S1, mixing an iron source, a carbon source and a solvent, and reacting them under high temperature to obtain a solution A; Wherein, the iron source includes a 0-valent iron source and a +2-valent iron source, and the molar ratio of the 0-valent iron source to the +2-valent iron source is (0.5-2):1; S2, adding a sodium source and a phosphorus source to the solution A, reacting under high temperature to obtain a solution B; S3, adding a dispersant to the solution B, reacting under high temperature to obtain a solution C; S4, stirring solution C to a gel state under high temperature conditions, and drying to obtain a precursor; S5. After ball milling the precursor, pre-sintering at low temperature and sintering at high temperature under a protective atmosphere to obtain a sodium iron pyrophosphate material prepared based on the regulation of the valence state of the iron source.

[0007] The present invention adopts a standard stoichiometric ratio to avoid the iron defects in the NFPP pure phase material synthesized in a non-standard stoichiometric ratio, which leads to Fe 2+ with Fe 3+ Fewer redox transitions occur, which leads to capacity degradation. The present invention adopts both 0-valent iron source and +2-valent iron source, and combines the adjustment of process parameters to ensure that the valence composition of the iron source in the precursor is most consistent with the synthesis orientation of the pure phase of NFPP; wherein the valence of the iron element in the precursor is +2-valent and +3-valent. During the sintering process, Fe 2+ First, it reacts with phosphorus source and sodium source. At this time, the synthetic orientation of the material tends to be NFPP, and then Fe3+ The carbothermal reduction reaction converts it into Fe 2+ , and continue to react with the remaining phosphorus source and sodium source to generate NFPP and a small amount of m-NFP, which greatly improves the phase purity of the synthesized NFPP, while reducing the content of the inactive phase m-NFP in the material to an extremely small level, and ensures that no iron defects are generated, the capacity of the material will not decrease, and a high-purity sodium iron pyrophosphate positive electrode material is synthesized.

[0008] Further, in S1, the 0-valent iron source is iron powder, and the +2-valent iron source is one or more of ferrous sulfate, ferrous chloride, and ferrous acetate; And / or, the carbon source is one or more of citric acid, ethylenediaminetetraacetic acid, glucose, and ascorbic acid; and / or, the atomic molar ratio of iron in all the iron sources to carbon in the carbon sources is 1:(2.5-8); And / or, the reaction temperature is 70-90° C. and the reaction time is 3-7 h.

[0009] Further, in S2, the sodium source is one or more of sodium acetate, sodium dihydrogen phosphate, sodium carbonate, and sodium sulfate; And / or, the phosphorus source is one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and diammonium hydrogen phosphate; and / or, the ratio of the number of atomic moles of sodium in the sodium source, phosphorus in the phosphorus source, and iron in all the iron sources in step S1 is 4:4:3; And / or, the reaction temperature is 70-90° C. and the reaction time is 0.5-1.5 h.

[0010] Further, in S3, the dispersant is one or more of ethylene glycol, polyethylene glycol 200, and polyethylene glycol 400; and / or, the ratio of the number of moles of iron atoms in all iron sources to the number of moles of carbon atoms in the dispersant in step S1 is 1:1 to 2.5; And / or, the reaction temperature is 70-90° C. and the reaction time is 0.5-1.5 h.

[0011] Furthermore, in S1-S3, the reaction conditions under high temperature conditions are high temperature stirring and condensation reflux, and the stirring rate is 1000-2000 rpm.

[0012] Further, in S4, the temperature of the high temperature condition is 60-90°C; And / or, the stirring speed is 300-600 rpm, and the stirring time is 0.5-2 h; And / or, the drying temperature is 130-180° C. and the drying time is 8-14 h.

[0013] Furthermore, in S5, the rotation speed of the ball milling treatment is 500-700 rpm, the ball-to-material ratio is (12-16):1, and the ball milling time is 7-9 h.

[0014] Furthermore, in S5, the temperature of the low-temperature pre-calcination is 300-350° C., and the holding time is 3-5 h; And / or, the low-temperature pre-sintering is followed by cooling to below 100° C. and then high-temperature sintering; And / or, the high temperature sintering temperature is 500-575° C., and the heat preservation time is 10-13 h.

[0015] Furthermore, in S5, the protective atmosphere is one of argon, nitrogen, argon-hydrogen mixed gas, and nitrogen-hydrogen mixed gas.

[0016] The second aspect of the present invention provides a sodium iron pyrophosphate material prepared by the method described in the first aspect, wherein the molecular formula of the sodium iron pyrophosphate material is Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C.

[0017] The third aspect of the present invention provides the use of the sodium iron pyrophosphate material described in the second aspect in a positive electrode material for a sodium ion battery.

[0018] Beneficial effects of the present invention: The present invention adopts both a 0-valent iron source and a +2-valent iron source to regulate the valence state of the iron source in the precursor, change the generation orientation of the product during the synthesis process, greatly improve the purity of the synthesized NFPP pure phase material, and reduce the generation orientation of m-NFP, effectively reducing the material impurity problem caused by the generation of inactive phase m-NFP due to side reactions occurring during the synthesis process.

[0019] The present invention adopts a standard stoichiometric ratio to avoid the iron defects in the NFPP pure phase material synthesized in a non-standard stoichiometric ratio, which leads to Fe 2+ with Fe 3+ Fewer redox transitions occur, which leads to a capacity drop problem.

[0020] The present invention adopts the carbon coating layer as the conductive layer, which can effectively improve the electronic conductivity of the material surface; at the same time, in the material synthesis process, it acts as a reducing agent to play a carbon thermal reduction role.

[0021] The invention has abundant raw material sources, high safety, and is green and environmentally friendly. Meanwhile, the cost is much lower than that of sodium vanadium phosphate positive electrode materials and layered transition metal oxide positive electrode materials. The invention adopts a sol-gel method, is simple to operate, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solution of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is the XRD spectrum of the sodium iron pyrophosphate positive electrode material prepared by Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 of the present invention; Figure 2 The sodium iron pyrophosphate positive electrode material prepared by Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 of the present invention is applied to a charge and discharge curve of a sodium ion battery at a current density of 0.2 C and a voltage window of 1.5-4.2 V; Figure 3 It is a rate curve of the sodium iron pyrophosphate positive electrode material prepared by Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 of the present invention applied to a sodium ion battery at a current density of 0.1-20 C and a voltage window of 1.5-4.2 V; Figure 4 This is a 300-cycle long cycle diagram of the sodium iron pyrophosphate positive electrode material prepared by Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 of the present invention when applied to a sodium ion battery at a current density of 10 C and a voltage window of 1.5-4.2 V. DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0025] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, using a molar ratio of 0-valent iron source to +2-valent iron source of 6.5:3.5, specifically comprising the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.95:1.05:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.013 mol reduced iron powder (Fe), 0.007 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 2

[0026] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which differs from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 6:4, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.8:1.2:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.012 mol reduced iron powder (Fe), 0.008 mol ferrous sulfate (FeSO4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 3

[0027] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which differs from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 5.5:4.5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.65:1.35:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.011 mol reduced iron powder (Fe), 0.009 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 4

[0028] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 5:5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.5:1.5:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 ), 0.01 mol reduced iron powder (Fe), 0.01 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 5

[0029] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which differs from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 4.5:5.5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.35:1.65:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.009 mol reduced iron powder (Fe), 0.011 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 6

[0030] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 4:6, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.2:1.8:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.008 mol reduced iron powder (Fe), 0.012 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Example 7

[0031] This embodiment relates to a method for preparing sodium iron pyrophosphate material Na based on the regulation of iron source valence state. 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C method, which differs from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 3.6:6.5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:1.05:1.95:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.007 mol reduced iron powder (Fe), 0.013 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 1

[0032] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 10:0, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:3:0:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.02 mol reduced iron powder (Fe), 0.02 mol citric acid (C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 2

[0033] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 8:2, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:2.4:0.6:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.016 mol reduced iron powder (Fe), 0.004 mol ferrous sulfate (FeSO4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 3

[0034] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 7.5:2.5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:2.25:0.75:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.015 mol reduced iron powder (Fe), 0.005 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 4

[0035] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 7:3, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:2.1:0.9:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.014 mol reduced iron powder (Fe), 0.006 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 5

[0036] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 3:7, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:0.9:2.1:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.006 mol reduced iron powder (Fe), 0.014 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 6

[0037] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 2.5:7.5, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:0.75:2.25:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.005 mol reduced iron powder (Fe), 0.015 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 7

[0038] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 2:8, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:0.6:2.4:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.004 mol reduced iron powder (Fe), 0.016 mol ferrous sulfate (FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Comparative Example 8

[0039] This comparative example relates to a sodium iron pyrophosphate material Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7) / C, which is different from Example 1 in that the molar ratio of the 0-valent iron source to the +2-valent iron source is 0:10, and specifically comprises the following steps: (1) According to the atomic molar ratio of Na:Fe(0):Fe(+2):P:C=4:0:3:4:18, weigh 0.02667 mol of sodium dihydrogen phosphate (NaH 2 PO 4 )、0.02 mol ferrous sulfate(FeSO 4 )、0.02 mol citric acid(C 6 H 8 O 7 ); (2) Dissolve reduced iron powder, ferrous sulfate and citric acid in 60 ml of deionized water, stir and reflux at 80 °C for 6 h; (3) Add sodium dihydrogen phosphate, stir at 80 °C and reflux for 1 h; (4) Add 2 ml of dispersant ethylene glycol, stir at 80 °C and reflux for 1 h to form a uniform solution; (5) Stop condensation and reflux, stir the solution at 80 °C until it is in a gel state; dry the gel at 150 °C for 12 h to form a precursor; perform high-energy ball milling on the precursor at a high-energy ball milling speed of 600 rpm, a ball-to-material ratio of 15:1, and a time of 8 h; (6) The ball-milled precursor powder is placed in a mixture of argon and hydrogen (Ar / H 2 The reaction mixture was placed in a tubular furnace with a volume ratio of 95 / 5), the temperature was raised to 300 °C at a rate of 5 °C / min for low-temperature pre-sintering for 3 h, and then the temperature was cooled to below 100 °C with the furnace; the temperature was then raised to 550 °C at a rate of 5 °C / min for high-temperature calcination for 12 h, and then the furnace was cooled. The obtained product was ground to obtain the sodium iron pyrophosphate positive electrode material. Test Case

[0040] The sodium iron pyrophosphate positive electrode materials prepared in Example Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 were subjected to XRD testing, and their XRD diffraction peak patterns are as follows: Figure 1 As shown, it can be seen that all positive electrode materials meet the basic characteristics of the NFPP standard PDF card, and all have some m-NFP impurity phase. However, the m-NFP impurity phase in the positive electrode materials prepared in Example 1, Example 4, and Example 7 is relatively small, especially, the positive electrode material prepared in Example 4 contains only a very small amount of m-NFP impurity phase, that is, it has the highest NFPP phase purity. Application Examples

[0041] The sodium iron pyrophosphate positive electrode material prepared in Examples 1-7 and Comparative Examples 1-8 was used to assemble a sodium ion battery, with the prepared sodium iron pyrophosphate positive electrode material as the active material, Super P (SP) and Ketjen Black (KB) as the conductive agent, PVDF as the binder, N-methylpyrrolidone (NMP) as the organic solvent, and the active material: SP: KB: PVDF = 80: 5: 5: 10 mass ratio was used for slurrying, and the positive electrode sheet was coated on aluminum foil. The sodium metal sheet was used as the negative electrode, the glass fiber filter paper was used as the diaphragm, and the 1 mol / L NaPF6 solution (PC + 5% FEC solvent) was used as the electrolyte, and the CR2032 button battery was assembled in a glove box filled with argon.

[0042] After the sodium ion batteries assembled with the sodium iron pyrophosphate positive electrode materials prepared in Examples 1-7 and Comparative Examples 1-8 were left standing at room temperature for 10 h, charge and discharge tests were performed in a voltage window of 1.5-4.2 V. The test results are shown in Table 1.

[0043] Table 1

[0044] As can be seen from Table 1, the sodium ion battery assembled with the sodium iron pyrophosphate material prepared in Examples 1-7 has excellent charge and discharge performance, especially the sodium ion battery assembled with the sodium iron pyrophosphate material prepared in high-purity Example 4, which has the highest charge and discharge capacity at a low current density of 0.2 C and a high current density of 10 C, and has the highest capacity retention rate after 100 cycles at a low current density of 0.2 C, which is consistent with the XRD test results. This shows that the preparation of high-purity sodium iron pyrophosphate positive electrode material by valence state regulation under standard stoichiometric ratio can significantly improve the performance of the sodium iron pyrophosphate positive electrode material.

[0045] Attached Figure 2 The sodium iron pyrophosphate positive electrode material prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 is used in a sodium ion battery at a current density of 0.2 C and a voltage window of 1.5-4.2 V. Figure 1 Analysis of the phase purity of seven groups of positive electrode materials, from Figure 2 It can be seen that with the improvement of phase purity, the charge and discharge capacity of the material shows an increasing trend, among which high-purity phase Example 4 has the highest charge and discharge capacity. It shows that the preparation of high-purity sodium iron pyrophosphate positive electrode material by valence state regulation under standard stoichiometric ratio can significantly improve the performance of sodium iron pyrophosphate positive electrode material.

[0046] Attached Figure 3The rate curve of the sodium iron pyrophosphate positive electrode material prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 is applied to a sodium ion battery at a current density of 0.1-20 C and a voltage window of 1.5-4.2 V. Figure 1 Analysis of the phase purity of seven groups of positive electrode materials, from Figure 3 It can be seen that with the improvement of phase purity, the rate performance of the material tends to increase, among which high-purity phase Example 4 has the best rate performance, and can still have a discharge specific capacity of up to 81.8 mAh / g at a current density of 20 C. This shows that the preparation of high-purity sodium iron pyrophosphate positive electrode material by valence state regulation under standard stoichiometric ratio can significantly improve the performance of sodium iron pyrophosphate positive electrode material.

[0047] Attached Figure 4 The sodium iron pyrophosphate positive electrode material prepared in Comparative Example 1, Comparative Example 2, Example 1, Example 4, Example 7, Comparative Example 7, and Comparative Example 8 is applied to a sodium ion battery at a current density of 10 C and a voltage window of 1.5-4.2 V for 300 cycles. Figure 1 Analysis of the phase purity of seven groups of positive electrode materials, from Figure 4 It can be seen that as the phase purity increases, the high-rate long cycle performance of the material shows an improving trend, among which high-purity phase Example 4 has the best high-rate long cycle performance, with a discharge capacity of up to 91.1 mAh / g at a current density of 10 C, and after 300 cycles, it can still maintain a discharge capacity of 90.8 mAh / g, with a capacity retention rate of 99.67%. This shows that the preparation of high-purity sodium iron pyrophosphate positive electrode material by valence state regulation under standard stoichiometric ratio can significantly improve the performance of sodium iron pyrophosphate positive electrode material.

[0048] In summary, the present invention adopts a simple sol-gel method to prepare sodium iron pyrophosphate positive electrode material, and adopts 0-valent and +2-valent iron sources at the same time. By regulating the valence state of the precursor iron source, a high-purity sodium iron pyrophosphate positive electrode material is synthesized under a standard stoichiometric ratio. By comparing different embodiments and comparative examples, it can be seen that the NFPP phase of the sodium iron pyrophosphate positive electrode material synthesized by the present invention is high in purity, and the high-purity sodium iron pyrophosphate positive electrode material has a good crystallographic structure and excellent electrochemical properties.

[0049] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source, characterized in that: The steps include: S1, mixing an iron source, a carbon source and a solvent, and reacting them under high temperature to obtain a solution A; Wherein, the iron source includes a 0-valent iron source and a +2-valent iron source, and the molar ratio of the 0-valent iron source to the +2-valent iron source is (0.5-2):1; S2, adding a sodium source and a phosphorus source to the solution A, reacting under high temperature to obtain a solution B; S3, adding a dispersant to the solution B, reacting under high temperature to obtain a solution C; S4, stirring solution C to a gel state under high temperature conditions, and drying to obtain a precursor; S5. After ball milling the precursor, pre-sintering at low temperature and sintering at high temperature under a protective atmosphere to obtain a sodium iron pyrophosphate material prepared based on the regulation of the valence state of the iron source.

2. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S1, the 0-valent iron source is iron powder, and the +2-valent iron source is one or more of ferrous sulfate, ferrous chloride, and ferrous acetate; And / or, the carbon source is one or more of citric acid, ethylenediaminetetraacetic acid, glucose, and ascorbic acid; and / or, the atomic molar ratio of iron in all the iron sources to carbon in the carbon sources is 1:(2.5-8); And / or, the reaction temperature is 70-90° C. and the reaction time is 3-7 h.

3. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S2, the sodium source is one or more of sodium acetate, sodium dihydrogen phosphate, sodium carbonate, and sodium sulfate; And / or, the phosphorus source is one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, phosphoric acid, and diammonium hydrogen phosphate; and / or, the ratio of the number of atomic moles of sodium in the sodium source, phosphorus in the phosphorus source, and iron in all the iron sources in step S1 is 4:4:3; And / or, the reaction temperature is 70-90° C. and the reaction time is 0.5-1.5 h.

4. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S3, the dispersant is one or more of ethylene glycol, polyethylene glycol 200, and polyethylene glycol 400; and / or, the ratio of the number of moles of iron atoms in all iron sources to the number of moles of carbon atoms in the dispersant in step S1 is 1:1 to 2.5; And / or, the reaction temperature is 70-90° C. and the reaction time is 0.5-1.5 h.

5. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S4, the temperature of the high temperature condition is 60-90°C; And / or, the stirring speed is 300-600 rpm, and the stirring time is 0.5-2 h; And / or, the drying temperature is 130-180° C. and the drying time is 8-14 h.

6. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S5, the rotation speed of the ball milling treatment is 500-700 rpm, the ball-to-material ratio is (12-16):1, and the ball milling time is 7-9 h.

7. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S5, the temperature of the low-temperature pre-calcination is 300-350°C, and the holding time is 3-5 hours; And / or, the low-temperature pre-sintering is followed by cooling to below 100° C. and then high-temperature sintering; And / or, the high temperature sintering temperature is 500-575° C., and the heat preservation time is 10-13 h.

8. The method for preparing sodium iron pyrophosphate material based on the regulation of the valence state of the iron source according to claim 1, characterized in that: In S5, the protective atmosphere is one of argon, nitrogen, argon-hydrogen mixed gas, and nitrogen-hydrogen mixed gas.

9. A sodium iron pyrophosphate material prepared by the method according to any one of claims 1 to 8, characterized in that: The molecular formula of the sodium iron pyrophosphate material is Na4Fe3(PO4)2(P2O7) / C.

10. Use of the sodium iron pyrophosphate material according to claim 9 in a positive electrode material for a sodium ion battery.

Citation Information

Patent Citations

  • Positive pole piece and preparation method thereof, energy storage device and power utilization device

    CN116779847A

  • Preparation method of single crystal type sodium ion battery positive electrode material sodium ferric pyrophosphate

    CN117228646A

  • Sodium ion battery polyanion positive electrode material and preparation method thereof

    CN117525391A

  • Iron-based sodium pyrophosphate / C composite material and preparation and application thereof in sodium ion battery

    CN118108202A

  • Preparation method of sodium ferric pyrophosphate composite material

    CN118458724A

Cited By

  • Preparation method of pre-reduced composite sodium ferric phosphate and sodium ion battery prepared from pre-reduced composite sodium ferric phosphate

    CN122403397A